A Study of Acoustic Emission and Damage Evolution of Limestone under Different Stress Paths and Confining Pressures. (19th October 2021) - Zhao, Jianjun; Wan, Xun; Ji, Lan; Zhu, Jinshi; Dai, Xinran; Wang, Jun
Abstract : Buried depth is an important factor affecting the deformation and failure of gob surrounding rock. Basing on triaxial compression unloading test and acoustic emission (AE) of limestone under three different initial confining pressures (5 MPa, 10 MPa, and 20 MPa) and three different stress paths, we analyzed the deformation and failure characteristics and energy releasing process of the virgin rock, the gob overburden rock, and the gob sidewall rock with different buried depths (within 1000 m). The results showed that, with the increase of buried depth, the shear fracture mainly propagated and the failure mode of the gob sidewall rock changed from brittleness to plasticity; however, the gob overburden rock was all brittle failure. Compared with shallow buried depths, the energy releasing triggered by confining pressure reduction in deep buried depths was more concentrated and intense. Under the background of deep buried depths, the peak strength and residual strength of the gob sidewall rock were the lowest, and the damage variable was the largest. We proposed that the first "acute phase" of AE can be wielded as the precursor information of the gob sidewall rock failure and crack propagation of hydraulic fracturing. The findings of the study are beneficial for the disaster prevention and control of deep mining in mountainous area, as well as fracturing evaluation.